Phenolic profile and colour acquired by the wine spirit in the beginning of ageing: Alternative technology using micro-oxygenation vs traditional technology. (August 2019) - Canas, Sara; Caldeira, Ilda; Anjos, Ofélia; Belchior, A. Pedro
Abstract: Alternative technologies have been extensively investigated towards a more sustainable ageing of red wine, but few studies were made on wine spirits. Moreover, the effect of micro-oxygenation on wine spirits' ageing is still unknown. This work examined the effect of micro-oxygenation and wood staves applied in 1000 L stainless steel tanks versus 250 L wooden barrels on the phenolic composition and chromatic characteristics acquired by the wine spirit over the first six months of ageing. Two different kinds of wood, Limousin oak and chestnut, were used. Significantly higher total phenolic content and individual contents of low molecular weight phenolic compounds (syringic acid, ellagic acid, vanillin, syringaldehyde, coniferaldehyde, sinapaldehyde and umbelliferone) were obtained with micro-oxygenation and staves than with barrels, for both kinds of wood. Accordingly, greater colour evolution (lower lightness, higher saturation and higher intensities of red, yellow and brown hues) was achieved in the former. These results were ascribed to a faster extraction and its balance with several phenomena involving the wood-derived compounds in the specific environment created by the direct supply of oxygen. A synergistic effect between the alternative technology and the chestnut wood was also observed. Highlights: Micro-oxygenation combined with staves vs barrels in wine spirit ageing were compared. Alternative technology induced higher accumulation of phenolic compounds. Faster colour evolution was also promoted. Synergistic effect between alternative technology and chestnut wood was found.